The solar cycle 25 multi-spacecraft solar energetic particle event catalog of the SERPENTINE project - Dresing, N.; Yli-Laurila, A.; Valkila, S.; Gieseler, J.; Morosan, D. E.; Farwa, G. U.; Kartavykh, Y.; Palmroos, C.; Jebaraj, I.; Jensen, S.; Kühl, P.; Heber, B.; et al. (EDP Sciences, 2025)
Context. The solar energetic particle analysis platform for the inner heliosphere (SERPENTINE) project, funded through the H2020-SPACE-2020 call of the European Union's Horizon 2020 framework program, employs measurements of the new inner heliospheric spacecraft fleet to address several outstanding questions on the origin of solar energetic particle (SEP) events. The data products of SERPENTINE include event catalogs, which are provided to the scientific community. Aims. In this paper, we present SERPENTINE's new multi-spacecraft SEP event catalog for events observed in solar cycle 25. Observations from five different viewpoints are utilized, provided by Solar Orbiter, Parker Solar Probe, STEREO A, BepiColombo, and the near-Earth spacecraft Wind and SOHO. The catalog contains key SEP parameters for 25- 40 MeV protons, ~1 MeV electrons, and ~100 keV electrons. Furthermore, basic parameters of associated flares and type II radio bursts are listed, as are the coordinates of the observer and solar source locations. Methods. An event is included in the catalog if at least two spacecraft detect a significant proton event with energies of 25- 40 MeV. The SEP onset times were determined using the Poisson-CUSUM method. The SEP peak times and intensities refer to the global intensity maximum. If different viewing directions are available, we used the one with the earliest onset for the onset determination and the one with the highest peak intensity for the peak identification. We furthermore aimed to use a high time resolution to provide the most accurate event times. Therefore, we opted to use a 1-min time resolution, and more time averaging of the SEP intensity data was only applied if necessary to determine clean event onsets and peaks. Associated flares were identified using observations from near Earth and Solar Orbiter. Associated type II radio bursts were determined from ground-based observations in the metric frequency range and from spacecraft observations in the decametric range. Results. The current version of the catalog contains 45 multi-spacecraft events observed in the period from November 2020 until May 2023, of which 13 events were found to be widespread (observed at longitudes separated by at least 80 from the associated flare location) and four could be classified as narrow-spread events (not observed at longitudes separated by at least 80 from the associated flare location). Using X-ray observations by GOES/XRS and Solar Orbiter/STIX, we were able to identify the associated flare in all but four events. Using ground-based and space-borne radio observations, we found an associated type II radio burst for 40 events. In total, the catalog contains 142 single event observations, of which 20 (45) have been observed at radial distances below 0.6 AU (0.8 AU). It is anticipated that the catalog will be extended in the future.